3D microfabricated scaffolds and microfluidic devices for ocular surface replacement: a review - Prina, Elisabetta; Mistry, Pritesh; Sidney, Laura E.; Yang, Jing; Wildman, Ricky D.; Bertolin, Marina; Breda, Claudia; Ferrari, Barbara; Barbaro, Vanessa; Hopkinson, Andrew; Dua, Harminder S.; Ferrari, Stefano; et al. (Humana Press, 2017)
In recent years, there has been increased research interest in generating corneal substitutes, either for use in the clinic or as in vitro corneal models. The advancement of 3D microfabrication technologies has allowed the reconstruction of the native microarchitecture that controls epithelial cell adhesion, migration and differentiation. In addition, such technology has allowed the inclusion of a dynamic fluid flow that better mimics the physiology of the native cornea. We review the latest innovative products in development in this field, from 3D microfabricated hydrogels to microfluidic devices.